Management počítačové sítě ISP - Svoboda, Filip (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Předmětem této bakalářské práce je management počítačové sítě poskytovatele připojení k internetu v obci Boleradice. Na základě analýzy manažerských postupů bylo odhaleno slabé místo v monitoringu sítě. V rámci řešení byl zakoupen server, na který byl nasazen pokročilý monitorovací nástroj Nagios. Přínosem této práce je zvýšení efektivity a zkvalitnění managementu sítě a možnost rychleji reagovat na výpadky síťových zařízení.

The subject of this thesis is management of computer network managed by internet service provider in the village Boleradice. Based on the analysis of current management practices weakness in monitoring was revealed. In order to address this issue a server was purchased, on which was installed Nagios, an advanced monitoring tool. The benefit of this project is increased efficiency and improved management of the network and ability to quickly respond to outages of network devices.
ISP Network Management
Keywords: Management počítačové sítě; poskytovatel připojení; ISP; WinBox; monitoring; Nagios; Centreon; server; Computer network management; internet service provider; ISP; WinBox; monitoring; Nagios; Centreon; server